Caught in the Act: Live-Cell Imaging of Plant Meiosis - Prusicki, Maria Ada; Balboni, Martina; Sofroni, Kostika; Hamamura, Yuki; Schnittger, Arp (Frontiers in Plant Science, 2021)
Live cell imaging is a powerful method to obtain insights into cellular processes, especially with respect to their dynamics. This is in particular the case for meiosis, where chromosomes and other cellular components such as the cytoskeleton follow an elaborated choreography in relatively short time. Making these dynamics visible opens a door to a next level of understanding the regulation of meiosis and its underlying molecular forces. However, the analysis of meiosis by live cell imaging is challenging and especially in plants, a temporally resolved understanding of chromosome segregation and recombination events has been lagging behind. Recent advances in live cell imaging have now enabled the analysis of meiotic events in plants in real time. The development of these methods relies on the generation of reporter lines for meiotic regulators as well as on the establishment of ex vivo culture and imaging conditions, which stabilize the specimen and keep it alive for several hours up to days. By combining an overview over technical aspects of live cell imaging in plants with a summary of questions, which can be addressed by this powerful method, the aim of this review is to promote live cell imaging in many plants, not only Arabidopsis, and stimulate ideas on which topics can be addressed especially for the analysis of meiotic recombination.